Maisy's bedtime - Cousins,Lucy (London: Walker Books Ltd, 2011)
In Maisy's Bedtime, Maisy the mouse gets ready to go to sleep. She follows her bedtime routine step by step taking a bath, putting on pajamas, brushing her teeth, and reading a story before tucking into bed. With bright illustrations and simple language, the book helps young children understand and feel comfortable with bedtime routines.
Maisy$1 (Bs Bedtime by Lucy Cousins is a delightful and simple picture book designed for toddlers and preschoolers. Through the character of Maisy, a cheerful little mouse, the story gently guides young readers through a comforting bedtime routine. The colorful, bold illustrations and repetitive text make it easy for young children to follow along and engage with the story. It$1 (Bs an excellent book for helping kids develop good bedtime habits and easing them into a consistent nighttime routine in a fun and familiar way.s
Keywords: Self-care; Sleep hygiene; Bedtime routine